Structure Functions of Rotation Measures Revealing the Origin of Fast Radio Bursts - Rui-Nan Li; Zhen-Yin Zhao; Qin Wu; Shuang-Xi Yi; Fa-Yin Wang (The Astrophysical Journal Letters)
Structure function (SF) analysis is a powerful tool for studying plasma turbulence. Theoretically, the SF of Faraday rotation measure (RM) is expected to include a geometric component due to the relative orientation of sight lines through an ordered magnetic field. However, observational evidence for this component remains elusive. Here, we report that the SFs of the binary PSR B1744–24A and the repeating fast radio burst (FRB) 20201124A exhibit both a periodic geometric component, caused by binary orbital motion, and a flat statistical component. The statistical component, induced by stochastic fluctuations in electron density and magnetic field, aligns with RM scatter derived from pulse depolarization. These findings indicate that FRB 20201124A has a binary origin and suggest that the periodic geometric component can serve as a diagnostic tool to identify binary companions.